The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5055/jom.2018.0451
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of naloxegol for opioid-induced constipation assessed by specific opioid medication, opioid dose, and duration of opioid use

Abstract: Objective: Efficacy and safety of naloxegol, a peripherally acting μ-opioid receptor antagonist that significantly reduces opioid-induced constipation (OIC), were assessed for patient subgroups defined post hoc by baseline maintenance opioid characteristics.Design: Post hoc, pooled analysis of data from two 12-week, randomized, double-blind, placebo-controlled, phase 3 studies.Setting: Two hundred fifty-seven outpatient centers in the United States and Europe.Patients: Patients with noncancer pain and OIC.Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…It was important to reduce opioid consumption because it has some side effects such as addiction, nausea, vomiting, constipation, and so on. In our study, there was a lower incidence of constipation, which may be the result of lower morphine consumption 27…”
Section: Discussionsupporting
confidence: 52%
“…It was important to reduce opioid consumption because it has some side effects such as addiction, nausea, vomiting, constipation, and so on. In our study, there was a lower incidence of constipation, which may be the result of lower morphine consumption 27…”
Section: Discussionsupporting
confidence: 52%
“…A recent retrospective analysis of 1,300 patients revealed that 25 mg naloxegol had similar efficacy in treating OIC regardless of the maintenance opioid type, dose, or duration of opioid use at baseline [70].…”
Section: Main Bodymentioning
confidence: 99%